Can technology change the existing culture? Case study on Bangladesh's public sector. Issue 1 (2nd January 2018) - Husain, Matt; Kolesar, Sebastian
ABSTRACT: This article highlights the challenges development aid donors can face in Bangladesh's post-colonial culture, as well as substantiating how lack of quality control in an aid project can influence local values, beliefs, and subjective experiences. The article also suggests that improving quality control, such as through monitoring and evaluation (M&E), can generate greater impact of development aid resources.